1974
DOI: 10.1021/j100596a023
|View full text |Cite
|
Sign up to set email alerts
|

Laser Raman spectra of species adsorbed on oxide surfaces. II

Abstract: In this paper we extend our investigation of the Raman spectra of pyridine over oxides. It is demonstrated that it is feasible to distinguish between the heterocycle a t Lewis or Bronsted and H-bonded sites on the surface. With recent improvements in technique, fluorescence is no longer a major problem while sensitivity is comparable with that found in the infrared. We demonstrate that the Raman method is rapid and can be applied repetitively to samples appropriate to isotherm measurement. We also demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…The ''Raman background'' or so-called ''fluorescence background'' has been a major hindrance to the application of Raman spectroscopy in studying not only solid catalysts 2,6,84 but also a wide variety of other materials such as biomolecules, 85,86 plant cells, 87 polymers, 88 paintings and textiles, 89 biomedical, [90][91][92] pharmaceutical, 92,93 and forensic materials. 94 The background has been widely attributed to fluorescence since the early Raman studies of oxide surfaces 95,96 and biopolymers and proteins. 97 However, a strong anharmonic interaction has also been suggested as an alternative to fluorescence.…”
Section: Uv Raman and The Problem Of Raman Backgrounds 41 Three Sourc...mentioning
confidence: 99%
“…The ''Raman background'' or so-called ''fluorescence background'' has been a major hindrance to the application of Raman spectroscopy in studying not only solid catalysts 2,6,84 but also a wide variety of other materials such as biomolecules, 85,86 plant cells, 87 polymers, 88 paintings and textiles, 89 biomedical, [90][91][92] pharmaceutical, 92,93 and forensic materials. 94 The background has been widely attributed to fluorescence since the early Raman studies of oxide surfaces 95,96 and biopolymers and proteins. 97 However, a strong anharmonic interaction has also been suggested as an alternative to fluorescence.…”
Section: Uv Raman and The Problem Of Raman Backgrounds 41 Three Sourc...mentioning
confidence: 99%
“…Therefore, the strong bond at 996 cm À1 is associated with the totally symmetric ring breathing mode due to the presence of the free TBP and physisorbed TBP, while the vibration of the trigonal symmetry ring stretching mode is too weak to identify. The medium intense bond at 1022 cm À1 is associated with the trigonal symmetry ring stretching mode owing to the presence of the coordinated TBP, whereas the vibration of the totally symmetric ring breathing mode shifts from 996 to 1007 cm À1 [19][20][21][22][23], and the scattering intensity of 1007 cm À1 is weaker than 1022 cm À1 . This demonstrates that some titanium atoms on the surface of nanocrystalline TiO 2 powder are incompletely coordinated, and can bind TBP molecules by forming Ti N bonds.…”
Section: Measurementsmentioning
confidence: 99%
“…This by comparison between polystyrene and pyridine second band is probably due to the pyridine ring binding by hydrogen bonds to a surface OH group literature spectra [15][16][17] (silanol). 18 In a work on pyridine adsorbed onto the 1004 cm 01 band remains. Thus, this study confirms the two kinds of P4VP populations adsorbed silica, Hendra et al showed that the pyridine Raman spectrum changes as the pyridine is desorbed onto the transparent beads: P4VP chemically adsorbed by ring/silica interactions and P4VP phys-from silica.…”
Section: P4vp-coated Silicamentioning
confidence: 99%